Antimicrobial activity of puffball(Bovistella radicata) and separation of bioactive compounds - Yong Ye; Kun Liu; Qinghua Zeng; Qingmei Zeng (AMB Express, 2017)
Abstract Background To test the antimicrobial activity of different extracts and fermentation broth from puffball(Bovistella radicata), the different extracts and fermentation broth of puffball were prepared, the active fraction was investigated by UPLC–UV–MS and semi-preparative chromatograph. Results Through zones of inhibition (ZOI) and minimum inhibitory concentrations (MIC) tests, the supernatant of fermentation possessed best antimicrobial activity in all extracts whose MIC value is 31.2 μg/ml against T. rubrum, T. mentagrophytes, S. aureus and P. aeruginosa. And ZOI value is 29.01, 21.02, 35.02, 28.01 mm against T. rubrum, T. mentagrophytes, S. aureus and P. aeruginosa. Then we compare the puffball fermentation supernatant with blank contrast by LC–MS. There are the characteristic peaks named PBR-1 and PBR-2 with the puffball fermentation supernatant, the separation of compound PBR-1 and PBR-2 was done on semi-preparative C18 column and the MIC and ZOI of compound PBR-1 and PBR-2 are 15.6 μg/ml and 34 mm with the antifungal test. Conclusions The fermentation supernatant and compound PBR-1 and PBR-2 have promising antifungal activity against T. rubrum and T. mentagrophytes.